BUDAYA MUTU SEBAGAI REFLEKSI DARI PPEPP DAN EPP DI AKADEMI MILITER MAGELANG - Dwi Joko Siswanto; Frangky Silitonga (PPM Sdirjianbang Akademi Militer, 2023)
The purpose of this article is to provide an overview of PPEPP culture in Akmil institutions in general. Problems related to the sustainability of PPEPP can be seen in EPP. Internal quality assurance at the Military Academy is an educational quality assurance activity that is carried out autonomously or independently to implement, control and improve the implementation of education for cadets in a planned and sustainable manner. The principle of autonomy/independence emphasizes that the Military Academy must develop its own Internal Quality Assurance System (SPMI) in accordance with the historical background, the basic values ​​that animate its establishment, the number of study programs, human resources and facilities and infrastructure without interference from other parties. The basic thing that must be in SPMI is that quality assurance is carried out through 5 (five) main steps, namely Determination, Implementation, Evaluation, Control and Improvement, which is abbreviated as PPEPP. PPEPP for each Dikti standard will produce kaizen or continuous quality improvement (CQI) on all Dikti standards, so as to create a culture of quality. The quality culture itself consists of mindset, attitude patterns and behavior patterns based on Dikti standards. Apart from measuring the quality of education at the Military Academy, the quality of education in the Military Academy is measured by fulfilling each Higher Education Standard, but it must also be measured by fulfilling the interactions between standards in the Military Academy, to create a Quality Culture.